A quantum chemical study on ˙Cl-initiated atmospheric degradation of acrylonitrile. Issue 33 (10th April 2017) - Sun, Jingyu; Shao, Youxiang; Wu, Wenzhong; Tang, Yizhen; Zhang, Yunju; Hu, Yiming; Liu, Jiangyan; Yi, Huiyang; Chen, Fang; Cheng, Yinfang
Abstract : Degradation of acrylonitrile (CH2 CHCN) by reaction with atomic chlorine was studied using quantum chemical methods. Abstract : Degradation of acrylonitrile (CH2 CHCN) by reaction with atomic chlorine was studied using quantum chemical methods. Density functional theory (DFT) (B3LYP, BHandHLYP, M11, MN12SX, M05-2X, and M06-2X) and Møller–Plesset perturbation theory (MP2) with the same basis set 6-311++G(d, p) were employed to obtain the geometries of intermediates and transition states. Potential energy surfaces (PESs) were characterized at the UCCSD(T)/cc-PVTZ//M05-2X/6-311++G(d, p) level. The dominant channel is the formation of the intermediate IM1(CH2 ClCHCN) by barrierless addition between ˙Cl and the terminal carbon atom of the CC double bond of acrylonitrile. Direct hydrogen-abstraction channels are negligible because of higher barriers and the endothermic process. The calculated rate constants were followed by means of the variational transition state theory by Variflex code, and these were in good agreement with the experimental values. The subsequent and secondary reactions for IM1(CH2 ClCHCN) involving NO and O2 molecules were also investigated in the atmosphere. The atmospheric lifetime of acrylonitrile in ˙Cl is about 18 h in the marine boundary layer. The contribution of ˙Cl to the transformation of acrylonitrile is comparative with that of the ˙OH. Thus, it is necessary to consider ˙Cl initiated tropospheric degradation of acrylonitrile.